New insights in the structural and morphological properties of sol-gel deposited ZnO multilayer films. (August 2016) - Demes, T.; Ternon, C.; Riassetto, D.; Roussel, H.; Rapenne, L.; Gélard, I.; Jimenez, C.; Stambouli, V.; Langlet, M.
Abstract: This study shows how the structural and morphological properties of sol-gel deposited ZnO films can be precisely tuned and selectively controlled. For that purpose, ZnO films have been deposited through a multilayer sol-gel route using solutions of zinc acetate dihydrate (ZAD) diluted in 1-butanol. The opto-geometrical, morphological, and structural properties of these films have been thoroughly studied in relation to the ZAD concentration in butanol, number of deposited single-layers, and heat-treatment conditions. On this basis, different physical processes occurring over the multilayer deposition procedure have been discussed to explain how the experimental parameters influence the film properties and enable to tune the grain size, texture coefficient, and surface coverage rate in a wide range of values. This work is a first step toward the optimized growth of ZnO nanowires on sol-gel films and their subsequent integration in 2D or 3D nanowire-based biosensors. Graphical abstract: Highlights: Multilayer ZnO films are deposited using a sol-gel route. Influence of experimental parameters on film properties is thoroughly investigated. Structural and morphological properties are tuned over a wide range of values. Grain size and texture coefficient of ZnO films are selectively controlled. The films are intended to serve as seed layers for further growth of ZnO nanowires.